2012
DOI: 10.1007/s10695-012-9621-5
|View full text |Cite
|
Sign up to set email alerts
|

The yellow catfish, Pelteobagrus fulvidraco (Siluriformes) metallothionein cDNA: molecular cloning and transcript expression level in response to exposure to the heavy metals Cd, Cu, and Zn

Abstract: Metallothionein (MT) has been used extensively as a potential molecular biomarker to detect heavy metal pollution in aquatic organisms. In order to investigate the modulation effect of heavy metals and to establish suitable biomarkers for the monitoring of heavy metal pollution, Pelteobagrus fulvidraco metallothionein gene was characterized as the first report in the family Bagridae. Pf-MT transcript was detected at high levels in liver, gonad, kidney, and brain compared to other tissues. A time-course study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 62 publications
0
15
1
Order By: Relevance
“…Metal accumulation relies on tissue metabolism and differences in their chemical environment, including presence of various ligands, each with different metal-binding characteristics (Campenhout et al, 2004). Different extent of tolerance of each fish species to different heavy metals may also induce different expression level of MTs (Boeck et al, 2003;Kim et al, 2012). Notably, differential regulation of metallothionein by various metals has been revealed in many other fish species (Cho et al, 2005).…”
Section: The Influence Of Some Heavy Metals On Aquatic Vertebratementioning
confidence: 99%
“…Metal accumulation relies on tissue metabolism and differences in their chemical environment, including presence of various ligands, each with different metal-binding characteristics (Campenhout et al, 2004). Different extent of tolerance of each fish species to different heavy metals may also induce different expression level of MTs (Boeck et al, 2003;Kim et al, 2012). Notably, differential regulation of metallothionein by various metals has been revealed in many other fish species (Cho et al, 2005).…”
Section: The Influence Of Some Heavy Metals On Aquatic Vertebratementioning
confidence: 99%
“…Using the blast algorithm of the National Center for Biotechnology Information (NCBI), we found that MT amino acids displayed high This high degree of similarity suggests that this highly conserved amino acid sequence may play the same role in Z. platypus as in other fish species. The high proportion of cysteine residues organized in Cys-Cys and Cys-X-Cys motifs is a typically specific characteristic of MT (Cho et al 2008;Kim et al 2012). In this study, MT amino acid sequence in Z. platypus also retained the specific common feature of MT.…”
Section: Resultsmentioning
confidence: 55%
“…In this study, MT amino acid sequence in Z. platypus also retained the specific common feature of MT. MT of Z. platypus consists of 20 cysteine residues among encoding 60 amino acids (approximately 33.3 %), similar to MT of yellow catfish, Pelteobagrus fulvidraco (Kim et al 2012). Cysteine motifs provide the binding capacity to heavy metals through the thiol group of its cysteine and make MT delay the acute toxicity of heavy metals (Ghedira et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations